Dual-emission Eu-doped Ca2−xSrxPN3 nitridophosphate phosphors prepared by hot isostatic press. Issue 26 (16th June 2021) - Fang, Mu-Huai; Hsueh, Hsi-Ping; Vasudevan, Thangaraji; Huang, Wen-Tse; Bao, Zhen; Majewska, Natalia; Mahlik, Sebastian; Sheu, Hwo-Shuenn; Liu, Ru-Shi
Abstract : Here, we demonstrate a series of Ca2− x Sr x PN3 :Eu 2+ nitridophosphate phosphors synthesized through a hot isostatic press with unexpected dual-emission in the red and infrared regions. Abstract : Nitridophosphates are regarded as an emerging compound class with applications in phosphor-converted light-emitting diodes. In this work, we aim to develop a series of Ca2− x Sr x PN3 :Eu 2+ nitridophosphate phosphors through a solid-solution strategy involving a hot isostatic press. Unexpected dual emissions in the red and infrared regions are observed, different from previous research results. The unique change in red and near-infrared emission with the incorporation of Sr 2+ is revealed and explained in detail through the structural analysis of the locally coordinated environment. Thermal properties including temperature-dependent photoluminescence and decay, as well as electron-lattice relaxation properties, are analyzed in detail. Furthermore, photobiomodulation based on the dual emission of Ca2− x Sr x PN3 :Eu 2+ in the red and near-infrared regions is proposed, demonstrating their potential practical applications. This study provides insight into the analysis of nitridophosphate phosphors and the development of novel luminescent materials.